Conformance of navigational behavioural to requirements using animation. (1st January 2012) - Dargham, Joumana; Semaan, Rima; Mcheick, Hamid
The web has become closely ingrained with our life and massive effort for web development and maintenance continues to take place in an ad hoc manner, resulting in poor quality web systems and applications. Problems such as outdated or irrelevant information, difficulties in using the website, website crashes, and security breaches are common. We encounter these kinds of problems because web developers failed to address users' needs along with the improper appliance of the web engineering process in all its phases. As a consequence, web engineering and more precisely web requirements engineering is becoming of major importance in the web development process. In this context, this work tackles the validation of the navigational requirements of a web application. A methodology named NRVA is introduced in order to validate the navigational requirements for correctness, consistency, and completeness. It is based on the generation of an XML document defining the navigational rules of the application and used as input to the animator. The supporting tool to the approach does not only validate the correctness of the generated requirements, but also it aids to the elaboration and enhancement of those requirements through visualisation.